PENERAPAN TEKNOLOGI WEB DALAM SISTEM PEMESANAN MAKANAN (FOOD ORDER SYSTEM) SYSTEMATIC LITERATURE REVIEW - Nurhinaya, Nurhinaya; Dani, Ahmad; Awalya, Nurul; Ulfani, Tri; Musfida, Firdha; Tribuana, Dhimas (Plexi Digital Indonesia, 2025)
The rapid advancement of information and communication technology has transformed service and business systems, including the culinary sector. One notable innovation is the web-based food ordering system, which enables customers to order and pay online without being physically present at the restaurant. This study systematically reviews the implementation of web technologies in food ordering systems using the Systematic Literature Review (SLR) method. Twenty-five scholarly articles published between 2020 and 2025 were analyzed from Google Scholar, IEEE Xplore, and ScienceDirect. The findings indicate that Laravel (PHP), Node.js (JavaScript), and Django (Python) are the most commonly used frameworks. The latest trend involves Progressive Web Apps (PWA) and API integrations with digital payment and order-tracking systems. These implementations enhance operational efficiency, reduce order errors, and increase customer satisfaction. However, challenges remain in data security, system scalability, and user experience. This research concludes that web technology plays a vital role in supporting digital transformation in Indonesia’s culinary industry, especially among MSMEs and university cafeterias.